2015
DOI: 10.3109/0886022x.2015.1014756
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic complications associated with PR3-ANCA crescentic glomerulonephritis

Abstract: Hemorrhagic complications of anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis are life-threatening conditions. Of these, alveolar hemorrhage is the most common and well-described hemorrhagic complication and is a prominent component of the pulmonary-renal syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The detailed relationship between vasculitis and nontraumatic RSH has not been proven or fully discussed. Some non-traumatic RSH cases with vasculitis have been reported, including anti-neutrophil cytoplasmic antibody (ANCA) -associated vasculitis (7)(8)(9), systemic lupus erythematosus (SLE) (10)(11)(12)(13), and polyarteritis nodosa (14) (Table 2). Many of these patients had active vasculitis and received high-dose steroids either for the initial treatment or for recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed relationship between vasculitis and nontraumatic RSH has not been proven or fully discussed. Some non-traumatic RSH cases with vasculitis have been reported, including anti-neutrophil cytoplasmic antibody (ANCA) -associated vasculitis (7)(8)(9), systemic lupus erythematosus (SLE) (10)(11)(12)(13), and polyarteritis nodosa (14) (Table 2). Many of these patients had active vasculitis and received high-dose steroids either for the initial treatment or for recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of DAH is associated with higher mortality and is a predictor of poor outcome 1. Therefore, it is of utmost importance to establish the correct diagnosis and initiate the appropriate therapy as soon as possible 6…”
Section: Discussionmentioning
confidence: 99%
“…There were no preexisting medical comorbidities reported that would have predisposed her to an intracranial hemorrhage, suggesting that this was a complication of severe GPA. This complication has been reported in GPA in the nonpregnant population, however, is more common in MPA and EGPA [ 37 , 38 ]. The second maternal death was in the context of severe respiratory infection and ARDS as a complication of MPA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%